2014
DOI: 10.1136/gutjnl-2013-306531
|View full text |Cite
|
Sign up to set email alerts
|

Double oral esomeprazole after a 3-day intravenous esomeprazole infusion reduces recurrent peptic ulcer bleeding in high-risk patients: a randomised controlled study

Abstract: NCT01591083.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…T h e ne w e ngl a nd jou r na l o f m e dicine A trial compared once-daily with twice-daily proton-pump inhibitor dosing for 11 days (followed in both groups by 2 weeks of treatment with a proton-pump inhibitor once daily) in highrisk patients who had undergone infusion of a proton-pump inhibitor for 3 days. 32 This trial showed a significantly lower rate of ulcer rebleeding with twice-daily therapy than with oncedaily therapy (11% vs. 29%). Patients with low-risk clinical features (a normal heart rate and blood pressure and no major coexisting conditions), low-risk endoscopic findings (clean-base ulcers, erosions, or nonbleeding Mallory-Weiss tears), and outpatient support can be discharged home after endoscopy, and a regular diet can be resumed 33 (Fig.…”
Section: Endoscopymentioning
confidence: 83%
“…T h e ne w e ngl a nd jou r na l o f m e dicine A trial compared once-daily with twice-daily proton-pump inhibitor dosing for 11 days (followed in both groups by 2 weeks of treatment with a proton-pump inhibitor once daily) in highrisk patients who had undergone infusion of a proton-pump inhibitor for 3 days. 32 This trial showed a significantly lower rate of ulcer rebleeding with twice-daily therapy than with oncedaily therapy (11% vs. 29%). Patients with low-risk clinical features (a normal heart rate and blood pressure and no major coexisting conditions), low-risk endoscopic findings (clean-base ulcers, erosions, or nonbleeding Mallory-Weiss tears), and outpatient support can be discharged home after endoscopy, and a regular diet can be resumed 33 (Fig.…”
Section: Endoscopymentioning
confidence: 83%
“…Those with high risk endoscopic lesions and clinical features should receive high dose PPIs on days one to three as above, followed by twice daily oral PPI on days four to 14. This regimen is based on an RCT of 187 patients that showed significantly less rebleeding with twice daily versus once daily PPIs (relative risk 0.41, 0.18 to 0.93) during this period 96…”
Section: Post-endoscopic Managementmentioning
confidence: 99%
“…We estimated the rate of persistent major SRH at second-look endoscopy to be 18 % according to the average rebleeding rate (7.5 %) after the fourth day with current treatment protocols based on our previous trial 18 , and the average rebleeding risk was estimated to be 40 % with all major SRH cases 2 . In a prospective cohort study, assuming the proposed proportion exposed in the control group was 0.1 and that the proposed control-to-case ratio was 4.5 (0.82/0.18), the statistical power for detecting an odds ratio (OR) of three would be 80 % on the basis of 299 patients using a two-sided test at the α value of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…In a prospective cohort study, assuming the proposed proportion exposed in the control group was 0.1 and that the proposed control-to-case ratio was 4.5 (0.82/0.18), the statistical power for detecting an odds ratio (OR) of three would be 80 % on the basis of 299 patients using a two-sided test at the α value of 0.05. The estimated incidence of rebleeding during the first 72 hours before the schedule was proposed to be 5 % 8 18 , so at least 315 patients had to be included.…”
Section: Methodsmentioning
confidence: 99%